Thinking alike: two pathways to leadership-candidate opinion congruence. Issue 4 (2nd October 2018) - Lesschaeve, Christophe; van Erkel, Patrick F. A.; Meulewaeter, Conrad
ABSTRACT: This paper seeks to explain why party candidates and their party leadership have congruent policy positions or not. Despite its importance as a way through which parties are able to behave as a unitary actor, this congruence has never been studied as a dependent variable. We seek to fill this void in the literature. Our results suggest that leadership-candidate congruence comes about through two mechanisms: selection and learning. With selection, the party leadership aims to get those candidates elected whose policy preferences are congruent with the party line. Learning occurs through the process of socialization in which candidates assume the views of the party they work and candidate for as their own under. This happens under the pressure of cognitive dissonance. If a candidate learns about the position of the leadership and notices that they are incongruent, they may feel discomfort and change their opinion to be congruent with the party.